Atención odontológica en pacientes pediátricos con autismo - Paola Fernanda, Castelo Naula (2023)
ABSTRAC Castelo Naula, P. (2023). Dental care in pediatric patients with autism (Graduate thesis). National University of Chimborazo. Riobamba, Ecuador. The objective of this research work is to describe dental care in pediatric patients with autism through a bibliographic review, revealing the clinical characteristics of the patient with autism spectrum disorder, mentioning the oral characteristics of the patient with autism spectrum disorder and identifying the techniques most current dental management for a patient with autism spectrum disorder. To carry out this research, a bibliographic review type study was carried out of the main journals indexed in the world through scientific databases such as PubMed, Google Scholar, Scielo, Elsevier and Medigraphic during a period from 2013 to the year 2023, of which a total of 53 articles for carry out the investigation. As a result, it was found that dental care for autistic patients represents a challenge for dentists because both physical and emotional skills are required for their care. The main characteristic of autistic children lies in the lack of communication and little or no social interaction. which makes dental care more difficult for these patients. Nowadays, behavioral analysis techniques are presented such as Treatment and education of autistic children with associated communication problems (TEACCH), Applied behavioral analysis (ABA), Systematic desensitization (SD), Visual pedagogy that facilitate dental care Keywords: Autism spectrum disorder, dental care, care protocol